Chemical modification of silica gel with multidentate ligands for heavy metals removal. Issue 4 (20th January 2016) - He, Song; Zhao, Chungui; Yao, Peng; Yang, Suping
Abstract: Two kinds of silica-gel supported chelating adsorbents with different multidentate ligands were synthesized for heavy metals removal. The obtained adsorbents were named as SG-AD and SG-ASD. SG-AD was the silica-gel supported dithiocarbamate ligand adsorbent; SG-ASD was the silica gel-supported dithiocarbamate and Schiff's bases adsorbent. FT-IR analysis and thermogravimetry analysis were used to characterize the prepared adsorbents. Their adsorption properties of Pb(II), Hg(II), Cu(II), Zn(II), and Cd(II) were also investigated. The results showed that SG-AD and SG-ASD showed high performance toward Pb(II) and Hg(II) removal, especially toward Hg(II) removal. Adsorption kinetics suggested that the adsorption processes of Pb(II) and Hg(II) on SG-AD and SG-ASD were governed by film diffusion and followed a pseudo-second-order model. The Langmuir model and Scatchard model were applied to fit the experimental equilibrium data for SG-AD and SG-ASD. With increasing temperature, the adsorption capacities and affinity constants of SG-AD and SG-ASD for Pb(II) and Hg(II) were increased. SG-ASD which contained two kinds of multidentate ligands showed strong chelating affinity to Hg(II). Langmuir model and Scatchard model can be integrated in describing the processes of heavy metal adsorption.